The role of the internal system of the Iraqi parliament in activating the parliamentary performance - Moanes, Raheem; Bahjat, Maha (Journal of Legal Sciences, 2022)
The constitutional system in Iraq went to the necessity of the independence of the parliament in setting its internal system, for the purpose of organizing parliamentary work in parliament, so our research came to this decree (the role of the internal system of the Iraqi parliament in activating parliamentary performance), where the importance of this system is highlighted in the advancement of the reality of parliamentary work For members of the House of Representatives, in order to truly represent their constituents, as they are empowered to enable them to exercise the two most important functions. The first is to legislate laws, by discussing and adopting them within a reasonable timeframe, which contributes to expediting the approval of legislation that voters need, in addition to Setting the appropriate plans to draw the general policy of the state and directing the government to implement it in a manner that achieves the aspirations of the electorate, as well as discussing and approving the general budget within the specified time period. As for the second function, which is to monitor the actions and performance of the government, through discussing the ministerial curriculum and following up its implementation, and the effective contribution in preserving public money and holding the government accountable in the event of negative indicators in the state’s financial policy, the Parliament must have the necessary means to move the political responsibility of the government, Therefore, this study came to show the role of the internal system and its adequacy in activating these two functions for members of Parliament, which deputies must exercise with all care and sincerity in a manner that fulfills the aspirations of the voters who put their confidence in Parliament. The study was divided into three topics: The first deals with the role of the internal system of the Iraqi parliament in activating the legislative performance. The second dealt with the role of the internal system in activating the regulatory performance. And the third dealt with the role of the internal system in activating the regulatory performance.